The November 23rd, 1980 Irpinia-Lucania, Southern Italy Earthquake: Insights and Reviews 40 Years Later - Porfido, Sabina; Alessio, Giuliana; Gaudiosi, Germana; Nappi, Rosa; Michetti, Alessandro Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint "The November 23rd, 1980 Irpinia-Lucania, Southern Italy Earthquake: Insights and Reviews 40 Years Later" presents a collection of 13 scientific contributions proposed by 44 researchers with different expertise and multidisciplinary approach highlighting the most important aspects of the Irpinia-Lucania earthquake (Ms 6.9, Io X MCS) from a seismological and geological point of view, without neglecting the reconstruction of cultural heritage, the resilience of the population, and the socioeconomic development of the internal areas of the Southern Apennines after the earthquake. The 1980 earthquake struck Irpinia-Lucania region (Southern Italy) and it is remembered in Italy not only for being the strongest earthquake recorded in the last 100 years causing devastation of entire regions and severe loss of human life, but also for the destruction of the cultural heritage in the epicentral area. This volume, far from being exhaustive, nevertheless wants to be an important point of reference for the new generations of researchers who will have both a historical and multidisciplinary approach to the knowledge of this earthquake.